2016
DOI: 10.18632/oncotarget.10687
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα1 deletion in fibroblasts promotes tumorigenesis in athymic nude mice by p52-mediated elevation of erythropoietin and CDK2

Abstract: Angiogenesis is essential for tumor development. Accumulating evidence suggests that adenosine monophosphate-activated protein kinase (AMPK), an energy sensor and redox modulator, is associated with cancer development. However, the effect of AMPK on tumor development is controversial, and whether AMPK affects tumor angiogenesis has not been resolved. We show that deletion of AMPKα1, but not AMPKα2, upregulates non-canonical nuclear factor kappa B2 (NF-κB2)/p52-mediated cyclin-dependent kinase 2 (CDK2), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Incorrect chromosome separation would lead to cellular apoptosis or hyperproliferation. p52 knockdown by specific shRNA inhibits the enhanced colony formation of AMPKα1-deleted MEFs [35], suggesting that p52 upregulation plays a critical role in the hyperproliferation of AMPKα1-deleted MEFs. Additionally, AMPKα1 deletion-mediated chromosome missegregation-caused cellular hyperproliferation may be due to p21 reduction, which is consistent with p21 knockout and contributes to the growth of PLK4-overexpressing cells [50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorrect chromosome separation would lead to cellular apoptosis or hyperproliferation. p52 knockdown by specific shRNA inhibits the enhanced colony formation of AMPKα1-deleted MEFs [35], suggesting that p52 upregulation plays a critical role in the hyperproliferation of AMPKα1-deleted MEFs. Additionally, AMPKα1 deletion-mediated chromosome missegregation-caused cellular hyperproliferation may be due to p21 reduction, which is consistent with p21 knockout and contributes to the growth of PLK4-overexpressing cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wanted to know the underlying mechanism for PLK4 elevation in AMPKα1 −/− MEFs. Since it was reported that AMPKα1 deletion upregulates nuclear factor-kappa B2/p52 [35], we tested…”
Section: Plk4 Upregulation In Ampkα1 −/− Mefs Is P52-mediatedmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation of the aggressive role of AMPK α1 in NSCLC was consistent with previous findings (6,14). However, AMPK α1 has also been indicated as a tumor suppressor (15), and its deletion reportedly promotes cell proliferation and angiogenesis (16). This discrepancy in different cancer types may be the result of different tissue systems, in addition to different targets and associated pathways.…”
Section: Discussionmentioning
confidence: 99%